Телевізійна програма як засіб моніторингу потреб абітурієнтів - Вовк, Наталія; Нечиталюк, Влада; Кльокта, Сніжана (Видавництво Львівської політехніки, 2017)
This article analyzes the urgency of and prospects for the television program in today's society, opens up new possibilities of information products for monitoring problems of entrance campaign in higher education institutions.
Keywords: моніторинг; телевзійна програма; інформаційний простір; опитування; реклама; ефір; абітурієнти; тестування